EspB and HtpG interact with the type III-A CRISPR/Cas system of Mycobacterium tuberculosis - Shi, Mingmin; Zhang, Hongtai; Fleming, Joy; Wei, Wenjing; Chen, Hong; Dai, Xiaowei; Liu, Yi; Li, Chuanyou; Ran, Fanlei; Wu, Zhilong; Wang, Yaguo; Zhang, Xilin; et al. (Frontiers in Molecular Biosciences, 2023)
short palindromic repeat/CRISPR-associated protein (CRISPR/Cas) system consisting of a Csm1-5 and CRISPR RNA (crRNA) complex involved in the defense against invading nucleic acids. However, CRISPR/Cas system in the MTB still is clearly unknown and needs to be further explored.In our work, two non-Cas system proteins EspB and HtpG protein were found and identified by LC-MS/MS. The effect of EspB and HtpG on Type III-A CRISPR/Cas System of Mycobacterium tuberculosis was examined by using Plasmid interference assay and Coimmunoprecipitation analyses. We explored that EspB could interact with the crRNA RNP complex, but HtpG could inhibit the accumulation of the MTB Csm proteins and defense the mechanism of CRISPR/Cas system.The proteins ESAT-6 secretion system-1(Esx-1) secreted protein B (EspB) and hightemperature protein G (HtpG), which were not previously associated with CRISPR/Cas systems, are involved in mycobacterial CRISPR/Cas systems with distinct functions.EspB is a novel crRNA-binding protein that interacts directly with the MTB crRNP complex. Meanwhile, HtpG influences the accumulation of MTB Csm proteins and EspB and interferes with the defense mechanism of the crRNP complex against foreign DNA in vivo. Thereby, our study not only leads to developing more precise clinical diagnostic tool to quickly detect for MTB infection, but also knows these proteins merits for TB biomarkers/vaccine candidates.